TELOMERE LENGTH OF PERIPHERAL BLOOD MONONUCLEAR CELLS IS ASSOCIATED WITH DISCHARGE DISPOSITION IN OLDER TRAUMA PATIENTS. Issue 3 (26th March 2023) - Goswami, Julie; MacArthur, Taleen A.; Ramachandran, Dhanya; Mahony, Cillian R.; Howick, Annelise S.; Price-Troska, Tammy; Thompson, Riley J.; Spears, Grant M.; Bailey, Kent R.; Patnaik, Mrinal S.; Passos, Joao F.; Park, Myung S.; et al.
ABSTRACT: Introduction: Little is known regarding peripheral blood mononuclear cell telomere length (PBMC-TL) and response to traumatic injury. The objective of this study was to characterize the role of PBMC-TL in coagulation and clinical outcomes after injury. Methods: Plasma and buffy coats were prospectively collected from trauma patients and healthy volunteers. DNA was purified and PBMC-TL quantified by quantitative polymerase chain reaction. Thrombin generation kinetics were expressed as lag time (in minutes), peak height (in nanometers), time to peak (in minutes), and endogenous thrombin potential (in nM × min). Results are in median and quartiles [Q1, Q3]. P < 0.05 was considered significant (Wilcoxon rank sum testing). Results: Forty-two younger patients (21 [20, 22] years, 69% were male) and 39 older patients (62 [61, 64] years, 79% were male) were included. There was no significant difference in Clinical Frailty Scores between groups. Younger patients had longer total PBMC-TL (0.40 Mb [0.30, 0.49] vs. 0.29 Mb [0.23, 0.33], P < 0.001) and longer average PBMC-TL per chromosome (4.3 kb [3.3, 5.3] vs. 3.2 kb [2.5, 3.7], P < 0.001). When older patients were stratified by 50th percentile of PBMC-TL, there were no differences in thrombin generation; however, those with shorter telomeres were less likely to be discharged home (29% vs. 77%, P = 0.004). Older patients in the bottom quartile of PBMC-TL had shorter lag time (2.78 min [2.33, 3.00] vs. 3.33 min [3.24, 3.89], P = 0.030) and were less likely to be discharged home (22% vs. 90%, P = 0.006) than those in the top quartile of PBMC-TL. Multivariable logistic regression models revealed both increased age and shorter PBMC-TL to be independent predictors of discharge disposition other than home. Conclusion: In older trauma patients, shorter PBMC-TL is associated with accelerated initiation of thrombin generation and lower likelihood of being discharged to home.